Modulation analysis and optical solitons of perturbed nonlinear Schrodinger equation - Houwe, A.; Sabi'u, J.; Betchewe, G.; İnç, Mustafa; Doka, S. Y. (Soc Mexicana Fisica, 2021)
We investigate modulation analysis and optical solitons of perturbed nonlinear Schrodinger equation (PNLSE). The PNLSE has terms of cubic nonlinearity and self-steepening and spatio-temporal dispersion (STD). Proposed model has been studied by [14, 15] without self-steepening term. The presence of the STD can help to compensate the low GVD to the model. Bright and dark solitary waves, trigonometric, periodic and singular optical solitons are obtained by some expansion methods including exponential and sinh-Gordon. Obtained results will hold a significant place in the field of nonlinear optical fibers, where solitons are used to codify data.
Keywords: Optical soliton; perturbed nonlinear Schrodinger equation; instability modulation